Apoptotic Mechanisms of Quercetin in Liver Cancer: Recent Trends and Advancements - Gautam Sethi; Prangya Rath; Abhishek Chauhan; Anuj Ranjan; Renuka Choudhary; Seema Ramniwas; Katrin Sak; Diwakar Aggarwal; Isha Rani; Hardeep Singh Tuli (MDPI AG, 2023)
Due to rising incidence rates of liver cancer and worries about the toxicity of current chemotherapeutic medicines, the hunt for further alternative methods to treat this malignancy has escalated. Compared to chemotherapy, quercetin, a flavonoid, is relatively less harmful to normal cells and is regarded as an excellent free-radical scavenger. Apoptotic cell death of cancer cells caused by quercetin has been demonstrated by many prior studies. It is present in many fruits, vegetables, and herbs. Quercetin targets apoptosis, by upregulating Bax, caspase-3, and p21 while downregulating Akt, PLK-1, cyclin-B1, cyclin-A, CDC-2, CDK-2, and Bcl-2. Additionally, it has been reported to increase STAT3 protein degradation in liver cancer cells while decreasing STAT3 activation. Quercetin has a potential future in chemoprevention, based on substantial research on its anticancer effects. The current review discusses quercetin's mechanisms of action, nanodelivery strategies, and other potential cellular effects in liver cancer.